Financial Impact of Air Pollution on BPJS Health Budget: Case Study of Financial Impact Due to Increased Health Claims Due to Air Pollution - Alfiana; Irwan Moridu; Nurul Afifah (West Science Business and Management, 2023)
Air pollution poses a significant threat to public health and the financial sustainability of the healthcare system, especially in densely populated urban areas such as Jakarta, Indonesia. This study investigates the financial impact of air pollution on the BPJS Kesehatan budget in Jakarta, focusing on the increase in health claims caused by air pollution-related diseases. A mixed methods approach, including quantitative data analysis and qualitative insights from stakeholders, was used to provide a comprehensive understanding of the issue. The quantitative analysis showed a significant positive relationship between air pollution indicators (PM2.5, NO2) and health claims, as well as large direct and indirect costs associated with air pollution-related healthcare expenditure. Qualitative findings highlighted factors contributing to the increase in health claims, including worsening air quality, lack of preventive measures, and challenges in healthcare access. This research provides recommendations to policymakers to address air pollution, improve healthcare outcomes, and maintain the financial health of the BPJS Kesehatan system. This research underscores the urgency of addressing air pollution as a public health and economic necessity.